Analisis Efektivitas Pengelolaan Dana Kampung dan Partisipasi Masyarakat dalam Pembangunan di Kampung Sereh Distrik Sentani Kabupaten Jayapura Papua - Hana Margaretha Uamang; Marsi Adi Purwadi (Universitas Cenderawasih, 2025)
This study aims to analyze the effectiveness of village fund management and the level of community participation in development in Kampung Sereh, Sentani District, Jayapura Regency, Papua, as well as to identify inhibiting factors and strategies for improvement. The research method used a quantitative and qualitative approach involving 45 informants from village officials and community members from nine neighborhood units (RT). Data collection techniques included observation, interviews, and documentation, with quantitative data analysis using frequency distribution and qualitative analysis using the Miles-Huberman model. The results showed that community participation was fairly good, with an average positive response rate of 74.5%, but the effectiveness of village fund management remained less effective because only 40% of projects aligned with planning documents and only 45% of the community perceived economic benefits. The main inhibiting factors include the community's passive mindset, low synergy between the Village Head and Ondoafi (customary leader), lack of understanding by Regional Device Work Units (SKPD) regarding participatory planning, and the impact of the COVID-19 pandemic which cut the development budget from Rp597 million to Rp403 million. The strategies developed include strengthening community capacity, stakeholder coordination, transparency in fund management, strengthening bottom-up strategies, economic empowerment, and resolving customary land disputes. Keywords: Village Fund Effectiveness; Community Participation; Village Development